Representative Speech Acts as Representations of Social and Cultural Realities in the Film Almanya-Willkommen in Deutschland - Isnaeni, Isnaeni; Izzah, Nurul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research explores the use of representative speech acts as a means of portraying social and cultural realities in the film Almanya-Willkommen in Deutschland. Referring to Searle’s theory of speech acts, the study seeks to examine the forms, communicative functions, and illocutionary forces of representative utterances expressed by the characters. The study applies a qualitative descriptive design. Data were obtained through careful observation and transcription of selected dialogues, which were then analyzed from a pragmatic perspective. The analysis shows that representative speech acts in the film are employed to convey historical facts, describe social circumstances, affirm cultural identities, clarify traditions, and provide reasons for particular experiences. Through these utterances, the speakers demonstrate their commitment to the truth of what is stated, which constitutes a central feature of representative acts. At the same time, the film presents migration experiences and identity negotiation processes through statements that reflect both personal and collective realities. The findings suggest that representative speech acts in the film do more than communicate factual information. They also contribute to the construction of meaning related to belonging, cultural continuity, and intercultural interaction across generations. In this way, representative speech acts function as an important pragmatic device in shaping how social and cultural realities are expressed and understood within the narrative.